Comparative Dispute Management in Land Disputes: Court-annexed ADR in Malaysia and Japan - Oseni, Umar Aimhanosi; Kadouf, Hunud Abia (2012)
This paper provides a comparative study of sustainable dispute management practices in Malaysia and Japan. With a focus on land-related disputes, the tangible and measurable objectives of the study include the identification of common trends in court-annexed dispute management in Malaysia and Japan; sustainable practices in court-annexed ADR that would engender prudent land management; the rate of out-of-court settlement in land disputes and its impact on the interest of the parties and ends of justice; and some unique trends the two countries can learn from each other to ensure a sustainable case management programme for land-related disputes. This study utilizes both the doctrinal research method and the empirical method for the Japanese and Malaysian aspects respectively to establish the common trends between the two jurisdictions. The study is expected to show that a comparative study on court-annexed dispute management between the two Asian countries can help in defining new directions in law reforms for sustainable land disputes management in the two jurisdictions. Such settlement would bring about mutual satisfaction among the disputing parties, avoidance of appeal backlogs, and foster a sustainable peace within the environment.